Practice Literate Research: Turning the Tables - Mike Fisher (Social Work and Society, 2011)
Researchers complain how difficult it is to get practitioners and policymakers to use research. In contrast, this paper looks at the issues from the perspective of practice, and argues that it is the researcher's job to become more practice-literate, so that research begins with practice concerns and develops practice-based solutions. The paper explores the relationship between research and practice and suggests that research has insufficiently engaged with the nature of practice and practice knowledge. Using the Salisbury Statement on practice research (Salisbury Statement 2010) the paper offers a definition of practice research and analyses what would be required for an agenda for practice research. Finally the paper proposes five functions for practice research.